(untitled) (Desenvolvimento em Questão, 2025)
The role of public policies in the sustainable regional development of the Brazilian Amazon, with a focus on small enterprises that utilize medicinal plants and phytotherapeutics, is of paramount importance, as they can contribute to the bioproducts sector, considering both national and international markets. The research uses the New Economic Geography (NEG) theory as a theoretical foundation to understand the challenges and opportunities associated with the bioeconomy in the region. Structural obstacles, such as the lack of infrastructure and effective regulations, as well as the need for integration between traditional knowledge and modern science, are highlighted. Policies such as the National Policy on Medicinal Plants and Phytotherapeutics (PNPMF) are emphasized as essential tools for promoting sustainable biodiversity management, fair benefit-sharing, and technological innovation. Case studies are also presented to contextualize the application of NEG theory. Related to this research, it is concluded that the sustainable development of the Amazon requires coordinated actions between the government, private sector, and local communities, prioritizing strategies that balance environmental conservation and income generation, consolidating the region as a global bioeconomy hub.